Corruption Prevention Efforts in the National Strategic Program Through the Strategic Development Security Program - Nasrulloh, Rully; Widyawati, Anis; Nte, Ngaboawaji Daniel (Pandecta Research Law Journal, 2024)
This research examines the Strategic Development Security Program (SDSP) within Indonesia's National Strategy under President Joko Widodo's administration, focusing on its role in preventing corruption in national and regional strategic projects. The SDSP represents a novel approach that combines strategic development with advanced security frameworks, offering a comprehensive solution to corruption. This study employs normative research methods, including extensive library research, to analyze the SDSP's implementation, particularly the mechanisms established by the Attorney General's Office as outlined in the Guidelines Number 5 of 2023 and Technical Instructions Number B-1450/D/Ds/09/2023. The urgency of this research is underscored by the growing need to enhance transparency and accountability in development efforts, amid rising concerns over corruption's impact on governance and societal welfare. The SDSP's innovative integration of real-time monitoring, risk assessment, and adaptive policy measures is critical in addressing these challenges. The research highlights the effectiveness of the SDSP in securing strategic development projects and its alignment with official guidelines and procedural frameworks designed to prevent corruption. By evaluating the SDSP’s mechanisms and their practical application, this study contributes valuable insights into improving anti-corruption strategies and governance frameworks. The findings aim to inform policymakers, refine anti-corruption efforts, and offer a model for similar initiatives globally. The research underscores the importance of adaptive, integrated approaches to safeguarding institutional integrity and promoting sustainable development, thus providing a significant contribution to both national and international anti-corruption discourse.